2009
DOI: 10.1089/end.2008.0446
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Autoaugmentation in Dogs: Assessment of Different Laparoscopic Methods

Abstract: Laparoscopic bladder autoaugmentation is feasible in the canine model with and without the intravesical silicone balloon. The best way to perform the surgery was identified for both methods. Future studies can be developed using a uniform surgical technique, and the functional results will be comparable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Similar to our data, D'Ancona et al reported the successful application of an intravesical balloon to prevent the shrinkage by holding the formed pseudodiverticulum distended after the surgery. Lottmann reported the use of intravesical balloon application in children after autoaugmentation with considerable outcome 9, 14. In our study balloon insertion helped to achieve significantly higher capacities and compliance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to our data, D'Ancona et al reported the successful application of an intravesical balloon to prevent the shrinkage by holding the formed pseudodiverticulum distended after the surgery. Lottmann reported the use of intravesical balloon application in children after autoaugmentation with considerable outcome 9, 14. In our study balloon insertion helped to achieve significantly higher capacities and compliance.…”
Section: Discussionmentioning
confidence: 99%
“…An additional step to keep the initially achieved surface area of this noncontractible bladder segment and thus the bladder capacity was first described by Querne et al, by using an intravesical balloon. They showed that a balloon can be helpful to prevent the shrinkage of the surgically achieved diverticulum during autoaugmentation 9. As mentioned above to maintain the achieved bladder capacities after surgery we hypothesized that a balloon insertion can be beneficial.…”
Section: Introductionmentioning
confidence: 92%